2021
DOI: 10.1186/s40249-021-00893-6
|View full text |Cite
|
Sign up to set email alerts
|

Ecological and behavioural risk factors of scrub typhus in central Vietnam: a case-control study

Abstract: Background The risk factors for scrub typhus in Vietnam remain unknown. Scrub typhus caused by Orientia tsutsugamushi often presents as an undifferentiated febrile illness and remains under appreciated due to the limited availability of diagnostic tests. This tropical rickettsial illness is increasingly recognized as an important cause of non-malaria acute undifferentiated fever in Asia. This study aimed to investigate behavioural and ecological related risk factors of scrub typhus to prevent t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…Similar findings were reported in India [ 37 , 38 ], Laos [ 33 ] and the northeast and southern regions of Thailand [ 35 ], with low education levels being associated with greater risks of scrub typhus infection. In contrast, several studies conducted in Vietnam [ 41 ], Korea [ 42 ], and China [ 40 ] did not show any link between education level and scrub typhus infection. This might be because almost all participants had the same educational level, and thus, there may not be enough statistical power to detect differences.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Similar findings were reported in India [ 37 , 38 ], Laos [ 33 ] and the northeast and southern regions of Thailand [ 35 ], with low education levels being associated with greater risks of scrub typhus infection. In contrast, several studies conducted in Vietnam [ 41 ], Korea [ 42 ], and China [ 40 ] did not show any link between education level and scrub typhus infection. This might be because almost all participants had the same educational level, and thus, there may not be enough statistical power to detect differences.…”
Section: Discussionmentioning
confidence: 87%
“…Several studies also reported that wearing gloves could protect individuals from scrub typhus infection [ 11 , 45 ]. Other clothing has been reported to be protective against scrub typhus infection, including long sleeve garments, long pants, boots, and socks [ 11 , 40 , 41 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, females were found to have a higher prevalence of scrub typhus (57.5%) than males and it is almost similar to the reported proportion of 58.7% in Vellore 46 and 51.46% in Guangzhou, Southern China 39 . But a surveillance and case–control study done in Vietnam in 2021 reported less proportion of females being positive for scrub typhus (38.6%) 52 . In multivariate analysis, females had a higher chance of being positive for scrub typhus.…”
Section: Discussionmentioning
confidence: 99%
“…To prevent the spread of the disease, it is essential to implement precautionary measures aimed at controlling the rodent population in rural areas. According to a study in Vietnam, factors related to ecological and household hygiene were found to have a stronger association with ST infection compared to individual-level exposure activities in the highly endemic area 51 .…”
Section: Discussionmentioning
confidence: 99%